2020
DOI: 10.1101/2020.06.05.135392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of mitochondrial health from human peripheral blood mononuclear cells to cerebral organoids derived from induced pluripotent stem cells

Abstract: Mitochondrial health plays a crucial role in human brain development and diseases. However, the evaluation of mitochondrial health in the brain is not incorporated into clinical practice due to ethical and logistical concerns. As a result, the development of targeted mitochondrial therapeutics remains a significant challenge due to the lack of appropriate patient-derived brain 5 tissues. To address these unmet needs, we developed cerebral organoids (COs) from induced pluripotent stem cells (iPSCs) derived from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Confocal and two-photon imaging were used to demonstrate that the organoids exhibit progressive differentiation, robust integration, and survival within the host (Mansour et al, 2018). Two years later, Doung et al reported the first attempt at systematically tracking mitochondrial health, including their morphology, during the different stages of development in cerebral organoids cut in 100 μm slices and labeled with JC-1 (Duong et al, 2020). However, both CLSM and two-photon microscopy have several limitations when dealing with long-term live imaging experiments.…”
Section: Processing Of Mitochondria In Brain Organoidsmentioning
confidence: 99%
“…Confocal and two-photon imaging were used to demonstrate that the organoids exhibit progressive differentiation, robust integration, and survival within the host (Mansour et al, 2018). Two years later, Doung et al reported the first attempt at systematically tracking mitochondrial health, including their morphology, during the different stages of development in cerebral organoids cut in 100 μm slices and labeled with JC-1 (Duong et al, 2020). However, both CLSM and two-photon microscopy have several limitations when dealing with long-term live imaging experiments.…”
Section: Processing Of Mitochondria In Brain Organoidsmentioning
confidence: 99%